Studies On Photocatalytic Degradation Of Phenol In Waste Water In A Batch Reactor. - Enche Ab Rahim, Siti Kartini; Mohamed, Abdul Rahman; Talpa Sai, P. Sesha (2003)
Heterogeneous photocatalysis is a novel water purification method in the group of advanced oxidation technologies. A dimensionless mathematical model is developed for the photocatalytic degradation in a batch reactor.